A preliminary study on isomer-specific quantification of sialylated N-glycans released from whey glycoproteins in human colostrum and mature milk using a glycoqueuing strategy. (1st March 2021) - Jin, Wanjun; Li, Cheng; Zou, Meiyi; Lu, Yu; Wei, Ming; Nan, Lijing; Jia, Yue; Wang, Chengjian; Huang, Linjuan; Wang, Zhongfu
Highlights: Glycoqueuing strategy was used to quantify sialylated whey N -glycans in human milk. 23 α2, 6-linked sialylated N -glycan isomers were detected; 72% were fucosylated. 3 mono- and 4 bi-sialylated glycan isomers were first identified in human milk. Sialylated whey N -glycan content was 86.43% lower in mature than in colostrum milk. Abstract: Sialylated N-glycans are an integral component of whey proteins in human milk and play an irreplaceable role in infant growth and development. Currently, there are few studies on quantitative comparison of sialylated N -glycans in milk obtained at different lactation stages. Here, a preliminary isomer-specific quantification of whey sialylated N -glycans of human colostrum milk (CM) and mature milk (MM) was performed by using our recently developed glycoqueuing strategy. Such a preliminary comparison revealed that the whey sialylated N -glycan content was 86.4% lower in MM than in CM. Twenty-three α2, 6-linked sialylated N -glycan isomers were detected with no α2, 3-linked isomer observed. For the first time, three mono-sialylated and four bi-sialylated glycan isomers were reported. With the prolongation of lactation, the relative abundance of mono-sialylated glycans increased, whilst the relative abundance of bi-sialylated glycans decreased significantly. These findings contribute to the understanding of the structure–function relationship of sialylated N -glycans in the human whey fraction.